Les espaces du graffiti dans les capitales touristiques : l’exemple de Paris et Berlin - Julie Vaslin (EchoGéo)
Considering that Paris, whose buildings are widely classified as World Heritage by UNESCO, and Berlin, known for being "poor but sexy", are two European capitals with very contrasting images, this article seeks to nuance this opposition by comparing the modalities of the government of the public space in these two cities. Especially, the regulation of graffiti is revealing, in Paris as in Berlin, convergent processes of "aestheticisation" of public space. Erased in high tourist areas, graffiti is tolerated or even promoted in working class areas, where tourism develops off the beaten track. Taken in different timeframes, graffiti governance systems transit from one capital to another, in a game where cultural and touristic developments combine at the service of territorial attractiveness. Considered alternately as an allegory of disorder or as an emblem of alternative tourism, graffiti appears as a very good indicator of these processes.